2018
DOI: 10.1007/s00018-018-2763-6
|View full text |Cite
|
Sign up to set email alerts
|

RIPK4 activity in keratinocytes is controlled by the SCFβ-TrCP ubiquitin ligase to maintain cortical actin organization

Abstract: RIPK4 is a key player in epidermal differentiation and barrier formation. RIPK4 signaling pathways controlling keratinocyte proliferation and differentiation depend on its kinase activity leading to Dvl2, Pkp1 and IRF6 phosphorylation and NF-κB activation. However, the mechanism regulating RIPK4 activity levels remains elusive. We show that cultured keratinocytes display constitutive active phosphorylated RIPK4 while PKC signaling can trigger RIPK4 activation in various non-keratinocyte cell lines, in which RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
1
12
0
1
Order By: Relevance
“…PKCs could activate RIPK4, which then induced uncontrolled epidermal inflammatory responses (17). Transgenic mice with epidermal overexpressing RIPK4 reacted hypersensitively to PKC (12,17). This was in accordance with the finding that RIPK4 knockdown in normal keratinocytes hampered the expression of differentiation markers upon PKC activation (18).…”
Section: Ripk4-related Signaling Pathwayssupporting
confidence: 79%
See 2 more Smart Citations
“…PKCs could activate RIPK4, which then induced uncontrolled epidermal inflammatory responses (17). Transgenic mice with epidermal overexpressing RIPK4 reacted hypersensitively to PKC (12,17). This was in accordance with the finding that RIPK4 knockdown in normal keratinocytes hampered the expression of differentiation markers upon PKC activation (18).…”
Section: Ripk4-related Signaling Pathwayssupporting
confidence: 79%
“…However, understanding the activation mechanism of RIPK4 gives valuable information about how RIPK4 functions at the biochemical level and how it controls epidermal differentiation and carcinogenesis. Constitutively activated RIPK4 by PKC can be degraded by the SCF β– T r C P -mediated proteasomal degradation pathway to maintain cortical actin organization in cultured keratinocytes ( 17 ). β-TrCP, which regulates multiple signaling pathways controlling cell growth, survival, death, and differentiation, is found to be involved in the process of carcinogenesis ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to HaCaT cells, si‐RNA mediated depletion of endogenous RIPK4 in the HepG2 cell line did not show any effects on TGF‐β1‐induced 3TP‐Lux and ARE‐Lux reporter gene expression (Figure B, iii‐iv). It has been demonstrated that in non‐keratinocyte cell lines, RIPK4 was in the non‐phosphorylated (non‐active) form, in contrast to keratinocyte cell lines in which RIPK4 was present in both auto‐phosphorylated (active) and non‐phosphorylated (non‐active) forms (Tanghe et al, ). To evaluate the ineffectiveness of RIPK4 depletion on TGF‐β1‐induced 3TP‐Lux and ARE‐Lux reporter gene expression, we examined the phosphorylation status of overexpressed and endogenous RIPK4 protein in HepG2 cells along with HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
“…We would like to thank Dr. Corinne Rösselet and Prof. Dr. Wim Declercq, Ghent University, for gateway entry vectors with activated mutant PKCs [111]. pSpCas9(BB)-2A-GFP (PX458) was a gift from Feng Zhang (Addgene plasmid # 48138) [112].…”
Section: Acknowledgmentsmentioning
confidence: 99%